Mortalidade por câncer em trabalhadores de companhia geradora de eletricidade do Estado de São Paulo, Brasil Cancer mortality among electricity utility workers in a Southeastern region Brazil - Inês E. Mattos; Sérgio Koifman (Universidade de São Paulo, 1996)
Realizou-se a análise exploratória de um conjunto de atestados de óbito de eletricitários do Estado de São Paulo (Brasil), através da Razão de Mortalidade Proporcional (PMR) e da Razão de Mortalidade Proporcional por Câncer (PCMR). Foi observado um discreto excesso de mortalidade por todas as localizações de câncer (PMR 1,11; IC 95% 0,91-1,35), estatisticamente não significativo. Encontrou-se elevação da PCMR, estatisticamente significativa, para câncer de laringe (PCMR 2,04; IC 95% 1,05-4,20). Um excesso de óbitos, embora sem significação estatística, foi observado para cavidade oral/faringe, próstata, bexiga, cérebro e doença de Hodgkin. A análise por categorias de exposição estimada a campos magnéticos mostrou PCMRs persistentemente elevadas para cancêr de bexiga (PCMR 4,17; IC 95% 1,35-9,72), cérebro (PCMR 3,77; IC 95% 1,02-9,65) e doença de Hodgkin (PCMR 5,55; IC 95% 1,14-16,21), no grupo com exposição provavelmente alta. Uma comparação com a mortalidade por câncer, de um grupo de trabalhadores petroquímicos, mostrou mortalidade elevada por neoplasma de laringe (PCMR 3,51; IC 95% 1,75-6,28) e bexiga (PCMR 7,53; IC 95% 3,02-15,51). Para tumores de cérebro, observou-se PCMR de 0,74 (IC 95% 0,27-1,61). A number of epidemiologic studies have observed an association between exposure to 50-60 Hz electromagnetic fields and the development of specific types of cancer. In Brazil, a preliminary report from a study of electricity facility workers in Rio de Janeiro (RJ) has mentioned relatively similar results. An exploratory analysis of death certificates obtained from a sample of electricity workers in S. Paulo was made. Data was analysed by using the Proportional Mortality Ratio (PMR) and the Proportional Cancer Mortality Ratio (PCMR). A slightly elevated all-sites cancer mortality was observed among these workers (PMR 1.11; 95% CI 0.91-1.35). Site specific analysis has shown a statistically significant higher mortality of laryngeal cancer (PCMR 2.04; 95% CI 1.05-4.20). An excess of deaths was also seen for cancers of the buccal cavity/pharynx, prostate, bladder, brain and Hodgkin's disease, although the results lacked statistical significance. When analysed by categories of estimated exposure to magnetic fields, an excess of deaths from bladder cancer (PCMR 4.17; 95% CI 1.35-9.72), neoplasms of the brain (PCMR 7.7; 95% CI 1.02-9.65) and Hodgkin's disease (PCMR 5.55; 95% CI 1.14-16.21) was observed in the group with probably higher exposure to EMF. A comparison of cancer mortality between these workers and petrochemical employees has shown a higher PCMR for larynx tumours (PCMR 3.51; 95% CI 3.02-15.51) and bladder cancer (PCMR 7.53; 95% CI 3.02-15.51). For brain tumours, however, a PCMR of 0,74 (95% CI 0.27-1.61) was noted. Although restrictions related to sample size in the study and the lack of information about known confounders must be considered, the results of this study do not fully disagree with others previously mentioned in the literature.